Zuzanna Ewa Wojciechowska: Feminine and Masculine Patterns of (Re)Construction One's Own Biography in the Perspective of Occupational Change - Ewa Drzewek (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2018)
Doctorates